Penerapan Teori Pemidanaan Dalam Putusan Perkara Tindak Pidana Pemilu Tahun 2019 - Dahtiar Dahtiar (Jurnal Penegakan Hukum Indonesia, 2022)
In the context of criminal elections, we need to look at the practice and there will likely be doubts and questions about the actualization of the application of the Theory of Punishment in judges' decisions. Especially for South Kalimantan, it is interesting to conduct research and analysis of the extent to which judges (especially those handling cases of the 2019 Election Crime), are in the process of imposing the type and duration of the crime. The purpose of this study is to examine and analyze whether every decision of a District Court Judge in South Kalimantan who handles criminal cases in the 2019 elections already reflects the theory of punishment. In addition, this study is also aimed at studying and analyzing what theories of punishment are used or adhered to by district court judges in South Kalimantan who handle criminal cases of the 2019 elections. Using the normative method with a case approach by examining the decisions of the District Court in South Kalimantan in the 2019 Election crime case that has been decided by the judge by taking all election crime cases in South Kalimantan which are simplified to a total of 6 (six) District Court decisions. It was found that the Panel of Judges for election criminal sanctions, especially in the criminal verdict of the 2019 elections in South Kalimantan, combined the sanction of imprisonment (improsenment) and fine sanctions with the application of the Theory of Relative Punishment which is oriented towards the Theory of Deterrence and the Theory of Objectives.